2021
DOI: 10.3855/jidc.13958
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Zinc Oxide nanoparticles on Pseudomonas aeruginosa biofilm formation and virulence genes expression

Abstract: Introduction: Due to increased resistance to antimicrobial agents, infectious diseases remain a public health problem worldwide. The current study was designed to examine the effect of Zinc Oxide nanoparticles (ZnO–np) against the biofilm formation ability of P. aeruginosa clinical isolates and to study its effect on the expression level of the genes involved in biofilm formation and virulence factors production. Methodology: The MIC of ZnO–np against P. aeruginosa was determined by the broth micro dilut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…We found that the expression of the QS-regulated genes lasI , lasR , rhlI , rhlR , pqsR , and pqsA decreased following exposure to ZnO NPs at concentrations of 900 µg/ml. Abdelraheem and Mohamed 55 found that ZnO NPs greatly down-regulated biofilm and virulence gene expression in PA clinical isolates for all genes studied aside from the toxA gene, which was up-regulated. The fold change reduction in the quorum sensing genes ( LasR , rhlI , and pqsR ) following exposure to ZnO NPs were 10.4-, 6.3-, and 8.7-fold, respectively 55 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We found that the expression of the QS-regulated genes lasI , lasR , rhlI , rhlR , pqsR , and pqsA decreased following exposure to ZnO NPs at concentrations of 900 µg/ml. Abdelraheem and Mohamed 55 found that ZnO NPs greatly down-regulated biofilm and virulence gene expression in PA clinical isolates for all genes studied aside from the toxA gene, which was up-regulated. The fold change reduction in the quorum sensing genes ( LasR , rhlI , and pqsR ) following exposure to ZnO NPs were 10.4-, 6.3-, and 8.7-fold, respectively 55 .…”
Section: Discussionmentioning
confidence: 96%
“…Abdelraheem and Mohamed 55 found that ZnO NPs greatly down-regulated biofilm and virulence gene expression in PA clinical isolates for all genes studied aside from the toxA gene, which was up-regulated. The fold change reduction in the quorum sensing genes ( LasR , rhlI , and pqsR ) following exposure to ZnO NPs were 10.4-, 6.3-, and 8.7-fold, respectively 55 . The impact of ZnO NPs is possibly similar to that of silver NPs as both reduce the expression of lasR and rhlR , causing a disturbance in QS circuits and an ensuing decline in biofilm formation 56 .…”
Section: Discussionmentioning
confidence: 96%
“…The results revealed that ZnONPs showed very potent activity against the tested microbial biofilms. Also, Abdelraheem and Mohamed [70] ) and the release of Zn 2+ and Cd 2+ [205] ZnO nanostructures (ZnO-NSs) 70-80 S. aureus, S. typhimurium, P. vulgaris, and K. pneumoniae ROS damage to cell membranes [206] confirmed that ZnONPs significantly down-regulated the expression level of all biofilms and virulence genes of P. aeruginosa clinical isolates except the toxA gene.…”
Section: Antimicrobial Activity Of Znonpsmentioning
confidence: 88%
“…Also, ZnO NPs downregulated virulence genes lasA and exoS by 5.2 and 3.7-fold, respectively ( p-value < 0.008). In addition, the toxA gene was downregulated by 1.9-fold (p-value = 0.37) after ZnO NPs remediation, thus no statistically considerable upregulation was recorded 98 .…”
Section: Resultsmentioning
confidence: 95%